The brazilian higher education entrepreneurship: the recovery of the "old / new" theses of the World Bank - Xavier, Maria Valonia da Silva; Oliveira, Rogério Paes de; Paula, Alisson Slider do Nascimento de; Costa, Frederico Jorge Ferreira (Revista Hipótese, 2018)
The objective of the present work is to analyze the movement of the commodified expansion of the Brazilian HE and the BM guidelines. This is a bibliographical and documentary study. It was centered in the Marxist tradition, in which it understands the object as the unity of the diverse. It was found that the HE follows in the wake of the interests of entrepreneurs of education. The forms of privatization of public HEIs, in fact, reveal that this level of education is understood as an essential market niche for capital.
Keywords: High Education; Privatization; World Bank